Problematika Pelaksaan Kurikulum 2013 Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar Luar Biasa Negeri Kota Lubuklinggau - Fitriyani Fitriyani; Atika Atika; Zainal Azman; Taufik Mukmin (STAI Bumi Silampari, 2021)
Researchers conducted research at the Lubuklinggau City Special School in class 3C with intellectual disabilities and the researchers concluded that: the implementation of the 2013 curriculum in learning Islamic Religious Education for mentally retarded children at the Lubulinggau Special School is not entirely in accordance with the standards in the 2013 curriculum. attitudes and skills. Meanwhile, mastery of the material (knowledge) is not emphasized because of the limited abilities of students. Standard content, simplified Islamic Religious Education material, time allocation 3x40 minutes one meeting a week. Standard process, the learning process prioritizes direct practice, such as congregational prayer, reading the Koran and memorizing it, only 30% of the learning resources are printed books, and learning Islamic Religious Education is not only in class. The assessment is carried out by means of tests, midterm examinations, final semester examinations, and assessment of the learning process. the inhibiting factor is that students find it difficult to provide subject matter, insufficient facilities and infrastructure, only one teacher of Islamic Religious Education subject, and incomplete supporting books.